ANALISIS STRATEGI PEMASARAN EFEKTIF UNTUK MENINGKATKAN PENJUALAN PRODUK SOMETHINC MELALUI MEDIA SOSIAL - Ignasia, Elvaretta; Aisyah Kayla; Aufa Atqiya; Eva Khuzaifah (Universitas Haji Sumatera Utara, 2025)
Digital marketing is crucial for company growth in the digital era, with social media being a key platform for brand building, awareness, and customer base expansion. This study analyzes the role of influencers in